PENGEMBANGAN OBJEK WISATA ALAM CURUG JAMI DI DESA SUKAMAJU - Wardani, Ari Kusumah; Pramulya, Diwan; Azminur, Rismayanti; Azzahra, Zakia Fatimah; Meilasari , Sindy (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Curug Jami is one of the natural attractions located in Kujang Kulon Hamlet, Sukamaju Village, Cihaurbeuti District, Ciamis Regency. Curug Jami is one of the areas at the foot of Sawal mountain under the management of the Natural Resources Conservation Center (BKSDA) which is included in the Wildlife Sanctuary area. The purpose of this observation is to analyze the development of Curug Jami natural attractions in order to increase tourist attractiveness and contribution to the local economy. This observation was conducted in the Sukamaju Village area with a descriptive qualitative approach with data collection techniques used through unstructured interviews. The results of the observation show that the development of this tourist attraction requires synergy between the government, the community, and the private sector. The main factors that influence development include inadequate infrastructure, limited promotion, and local community awareness of tourism potential. The proposed strategies include improving accessibility through road improvements, expanding supporting facilities such as parking areas, providing campsites, and optimizing digital promotions. Sustainable cooperation between related parties is expected to improve the quality of tourist attractions, attract more visitors, and have a positive impact on the welfare of the surrounding community.